La Noire Idole : Opium, ivresse et ébriété au XIXe siècle aux Etats-Unis - Irène Delcourt (Nuevo mundo - Mundos Nuevos, 2016)
The concept of drunkenness is hardly a novelty in the 19th century. Defined as a physical and mental reaction to substance intoxication, it has assumed multiple forms and known many interpretations: social transgression, vice, disease, religious experience…Nevertheless, it is not before the 19th century that the question of inebriety begins to appear in the United States, in the larger context of social reform and particularly the Temperance Movement. Ultimately, it is the development of medical sciences and psychiatry in the second half of the century which truly transforms the perception and treatment of inebriety and inebriates. For the very first time, alcohol – and other consciousness-altering substances – intoxication is defined through the spectrum of disease rather than vice, and addiction is diagnosed. As such, the addict becomes a sick person and inebriety a symptom of his/her pathology, whose nature remains to be precisely characterised. However, if the outlook on addiction and inebriety evolves, it may very well be because of the observation of a new type of “drunkenness”, which differs in modality and representation from alcoholism: opiate inebriety, America’s new mal du siècle.